Patient Safety Climate: Variation in Perceptions by Infection Preventionists and Quality Directors - Shanelle Nelson; Patricia W. Stone; Sarah Jordan; Monika Pogorzelska; Helen Halpin; Megan Vanneman; Elaine Larson (Interdisciplinary Perspectives on Infectious Diseases)
Background. Healthcare-associated infections (HAIs) are an important patient safety issue, and safety climate is an important organizational factor. This study explores perceptions of infection preventionists (IPs) and quality directors (QDs) regarding two safety microclimates, Senior Management Engagement (SME) and Leadership on Patient Safety (LOPS), across California hospitals. Methods. This was an analysis of two cross-sectional surveys. We conducted Wilcoxon signed-rank test, univariate analyses, and a multivariate ordinary least square regression. Results. There were 322 eligible hospitals; 149 hospitals (46.3%) responded to both surveys. The IP response rate was 59%, and the QD response rate was 79.5%. We found IPs perceived SME more positively than did QDs (21.4 vs. 20.4, 𝑃<0.01). No setting characteristics predicted variation in perceptions. Presence of an independent budget predicted more positive perceptions of microclimates across personnel types (𝑃<0.01). Conclusions. Differences in perceptions continue to exist between essential leaders in acute health care settings which could have critical effects on outcomes such as HAIs. Having an independent budget for the infection prevention and control department may enhance the overall safety climate and in turn patient care.